FOXO 1 deletion in chondrocytes rescues diabetes-impaired fracture healing by restoring angiogenesis and reducing apoptosis - Alharbi, Mohammed A.; Graves, Dana T. (Frontiers in Endocrinology, 2023)
Diabetes mellitus is associated with higher risks of long bone and jaw fractures. It is also associated with a higher incidence of delayed union or non-union. We tested the hypothesis that FOXO1 plays a key role in diabetes-impaired angiogenesis and chondrocyte apoptosis. Type-1 diabetes was induced by multiple streptozocin (STZ) injections to mice with linage-specific FOXO1 deletion in chondrocytes (Col2α1Cre+.FOXO1L/L) or littermate controls, (Col2α1Cre-.FOXO1L/L). Diabetic mice had 50% fewer blood vessels compared to normoglycemic evaluated by immunofluorescence. FOXO1 deletion in diabetic mice partially rescued the low number of blood vessels (p < 0.05). Additionally, diabetes increased apoptotic chondrocytes by 50%. FOXO1 deletion in diabetic animals blocked the increase in chondrocyte apoptosis to levels comparable to normoglycemic animals (p < 0.05). High glucose (HG) and high advanced glycation end products (AGE) levels stimulated FOXO1 association with the caspase-3 promoter in vitro, and overexpression of FOXO1 increased caspase-3 promoter activity in luciferase reporter assays. Furthermore, we review previous mechanistic studies demonstrating that tumor necrosis factor (TNF) inhibition reverses impaired angiogenesis and reverses high levels of chondrocyte apoptosis that occur in fracture healing. Thus, new results presented here, in combination with recent studies, provides a comprehensive overview of how diabetes, through high glucose levels, AGEs, and increased inflammation, impair the healing process by interfering with angiogenesis and stimulating chondrocyte apoptosis. Moreover, FOXO1 in diabetic fractures plays a negative role by reducing new blood vessel formation and increasing chondrocyte cell death.